Breast liposarcoma with solitary metastasis to the pleura: A case report - Lei, Lei (Medicine (Baltimore), 2017)
RATIONALE: Breast cancer is the most prevalent malignancy in women worldwide. Our patient presented with a history of breast liposarcoma (LPS) and was found to have pleural metastasis during the initial workup. PATIENT CONCERNS: The patient was complaining about chest pain and dyspnea that had persisted for a week. DIAGNOSES: After a full evaluation and histological diagnosis, she was diagnosed as metastatic breast LPS. INTERVENTIONS: We adopted 6 cycles of pegylated liposomal doxorubicin (PLD) plus ifosfamide as 1st-line palliative chemotherapy, combined with local pleural effusion management. OUTCOMES: The patient's symptoms were notably relieved, and both malignant metastatic lesions and pleural effusion were controlled. LESSONS: Although metastatic breast LPS is rarely reported and incurable, more clinical experience and use of next-generation sequencing should be helpful in finding the effective treatment for metastatic LPS.